DIKSI DAN POLA SINTAKSIS DALAM PEPATAH ACEH - Teguh Santoso (Humaniora, 2007)
This paper aims at describing the diction and the sentence forms of Aceh’s aphorism. Aphorism is one of the Aceh culture used by society until now. Aphorism is sometimes used as a term to describe the way in which a person pronounces the words, particularly the degree of clarity of his or her speech.. In other words, as a communication model aphorism has a specific structure of syntax. Singular and plural syntax can be found in Aceh aphorism. The words may express many meanings such as comparison, confirmation, negation, and antonym.